Public Speeches of Vaclav Havel: Syntactic and Stylistic Aspects (Case Study of the President’s New Year Speeches) (Linguostylistic Studies, 2016)
The article deals with the syntactic and stylistic analysis of public speeches of the first President of Czech Republic Vaclav Havel, in particular his New Year speeches within the period of 1990-2003. The emphasis is laid on the stylistic devices and expressive means used by V. Havel in his New Year speeches, among which the most frequently used are metaphors, rhetorical questions, allusions (indirect references to the works of famous Czech personalities like J. A. Komensky) etc. The article also reveals the peculiar features of the syntax of President’s speeches. The findings of the study indicate to high extensiveness of syntactical constructions used in them with dominance of complex sentences, numerous constructions, which permit to avoid a great quantity of complex sentences. The results of the research determining the speech syntactic and stylistic characteristics of the worldwide known politician offer new opportunities to explore the peculiarities of an individual language use in the political discourse. Key words: public speech, political discourse, linguistic devices, the New Year speeches, syntactic and stylistic aspect. References